Protein evolution of ANTP and PRD homeobox genes. - Fonseca, N; Vieira, C; Holland, P; Vieira, J (2008)
BACKGROUND: Although homeobox genes have been the subject of many studies, little is known about the main amino acid changes that occurred early in the evolution of genes belonging to different classes. RESULTS: In this study, we report a method for the fast and efficient retrieval of sequences belonging to the ANTP (HOXL and NKL) and PRD classes. Furthermore, we look for diagnostic amino acid residues that can be used to distinguish HOXL, NKL and PRD genes. CONCLUSION: The reported protein features will facilitate the robust classification of homeobox genes from newly sequenced bilaterian genomes. Nevertheless, in non-bilaterian genomes our findings must be cautiously applied. In principle, as long as a good manually curated data set is available the approach here described can be applied to non-bilaterian organisms as well. Our results help focus experimental studies onto investigating the biochemical functions of key homeodomain residues in different gene classes.